Penilaian karektor landskap melayu di Pantai Barat Semenanjung Malaysia - Khamis, Hazel (2007)
This research on the character of the Malay Landscape covers the architecture of the landscape based on the functions and the culture. Two main and important components that lead to developing the Malay landscape are plants and garden furnitures. Each component has its own cultural and artistic values that vividly portray the symbol that exist in the Malay culture. The values of the Malay culture based on the belief and world of thought had been the foundation of the Malay cosmology. These values had been indirectly define in the research parameter through various aspect as the design, art, composition, symbol and the function. These elements also consist of indirect values and symbolisme that can be ascertained through the perception that are meant to be delivered either in the aspect of culture or its functions. The qualitative and quantitative methods had been used in the research to determined the elements and components of the Malay landscape both in the physical and metaphysical form. The quantitative method focus on the symbolisme in the Malay landscape through inventories and interviews with the respondent. Quantitatively, the research evaluates the statistical aspect of the landscape components that indicate the type, function and the overall resemblance. These research data obtained show the values in every elements which directly or indirectly proved the existance of the Malay landscape. Thus, the research shows that the character of the Malay landscape that has been identified could be used as a guideline for the Malay landscape design which is suitable in the present environment.